FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PERSONAL HYGIENE REMAJA PUTRI DALAM PENANGANAN DAN PENCEGAHAN KEPUTIHAN PADA SISWI SMK NEGERI 11 SEMARANG - Susanti Handayani; Kusyogo Cahyo; Ratih Indraswari (Jurnal Kesehatan Masyarakat (Undip), 2017)
One of adolescent reproductive health problems that need to be observed is a disease of reproductive tract infectios one of which is whitish.Physiologic vaginal discharge when behavior in reproduction health keeping is poorly in feminine area.The purpose of this study was to analyze the factors correlated with personal hygiene behavior of female adolescent in treatment and preventation vaginal discharge of SMK Negeri 11 Semarang students.The study was quantitative method with cross sectional approach. The number of samples were 70 students. The data was analyzed by chi-square.The result of this research showed that the majority of respondets had poor knowledge  (67,1%), had non-permissive attitude (72,1%), had poor acces to health service (62,9%), had poor information availability (54,3%), had mother's support is less supportive (91,4%), had poor behaviour (54,3%) about treatment and preventation vaginal discharge. The result of bivariate analysis showed that  knowledge (p= 0,042) correlates with  the personal hygiene behaviour of female adolescent in treatment and preventation vaginal discharge on the other hand, attitude (p=0,711), acces to health service (p=0,760),  information availability (p=0,587) and mother's support (p=0,516) does not correlates with  the personal hygiene behaviour of female adolescent in treatment and preventation vaginal discharge of SMK Negeri 11 Semarang.